Ancaman Dan Peluang Artificial Intelligence (AI) - Siti Masrichah (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
The use of artificial intelligence (AI) has brought significant changes in various aspects of human life. However, these advancements also pose challenges and opportunities that need to be well understood. This research discusses the threats and opportunities associated with the use of AI in various contexts, such as privacy, the labor market, healthcare, and renewable energy. The findings reveal that the use of AI in the collection and analysis of personal data can threaten individual privacy. Additionally, certain types of human jobs are at risk of being replaced by AI, necessitating the adaptation and development of new skills. However, AI also holds great potential in improving medical diagnosis and healthcare and optimizing the operations of renewable energy systems. Technical, ethical, and security challenges related to the use of AI must also be considered. Therefore, the use of AI must be conducted responsibly and based on strong ethical values. By understanding these challenges and opportunities, appropriate measures can be taken to maximize the benefits and mitigate the risks associated with the use of AI.